2006
DOI: 10.1007/s10439-006-9149-x
|View full text |Cite
|
Sign up to set email alerts
|

The Hemodynamics of the Berlin Pulsatile VAD and the Role of its MHV Configuration

Abstract: The 3D flow in a model of the Berlin ventricular assist device (VAD) chamber with monoleaflet valves placed in S-shape conduits was simulated numerically. The blood flow dynamics were described in terms of flow patterns, velocity, pressure, and shear stress. The hemodynamic properties and the VAD's potential risk for thrombosis were evaluated in terms of mixing and washout properties, and global estimations of platelet level of activation (LOA). In order to evaluate the role of valves on the flow in the chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…(10) alternatively. This has been used in several computational studies to calculate AP [9, 1, 133]. It should be noted however that for incompressible flow, σν=2μeF, and the two measures provide equivalent results.…”
Section: Tracking Cellular Damagementioning
confidence: 99%
See 1 more Smart Citation
“…(10) alternatively. This has been used in several computational studies to calculate AP [9, 1, 133]. It should be noted however that for incompressible flow, σν=2μeF, and the two measures provide equivalent results.…”
Section: Tracking Cellular Damagementioning
confidence: 99%
“…It should be noted however that for incompressible flow, σν=2μeF, and the two measures provide equivalent results. Some experimental studies have suggested that stress and exposure time should not be “weighted equally,” but AP is better expressed as a power law of stress and exposure time [53, 2, 55, 106], which has been applied in several computational studies [9, 1, 102, 153, 132, 133, 12, 93]. …”
Section: Tracking Cellular Damagementioning
confidence: 99%
“…For this research, valve closure is modeled using the variable viscosity model employed by Avrahami et al [20][21][22] and Stijnen [23,24]. The valve grids are fixed at the fully opened position for the duration of the analysis.…”
Section: Valve Closure Modelmentioning
confidence: 99%
“…Avrahami et al [20][21][22] performed an unsteady 3D analysis of a complete pumping cycle for several LVADs. The analysis assumed incompressible, Newtonian, and laminar fluid behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Changes to valve type and orientation have been established as methods to improve flow throughout VADs. 1,3,12,20 In a previous study by our lab we found that the blockage remained at all valve orientations, therefore we chose to move the valve position. The rationale of moving the valve downstream is that the flow can move from the body of the device to the smaller outlet port without the interference of the mechanical heart valve strut and disc.…”
Section: Introductionmentioning
confidence: 99%